The exile of Britney Spears : a tale of 21st century consumption - Smit, Christopher R. (Intellect, 2011)
"What we consume matters: a conclusion that is making more sense as sustainability and eco-responsibility become part of our everyday cultural conversations. What we fail to realize is that we consume -- unconsciously, continually, and, at times, violently -- much more than food. The Exile of Britney Spears: A Tale of Twenty-First Century Consumption explains that we have consumed, digested, and eliminated Britney Spears in a process uniquely characteristic of American popular culture. In Christopher Smit's explanation of the sociological, aesthetic, and political outcomes of this new mediated cannibalism; he offers the idea of exile as a new metaphor for the outcome of popular consumption. By investigating the psychological, personal and social matrix of Britney's rise and fall (and rise again?), he outlines the process of her inevitable exile from global taste and favour. While the book encourages the reader to see Britney's volition within her narrative, it ultimately works to explain the larger practices bound up with our consumption of her life within the malleable context of new media and digital communication"--Provided by publisher.